The A PRACTICAL APPROACH FOR SOFTWARE PROJECT MANAGEMENT - Vijay Bhardwaj, Sunny Arora (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Software project management is introduced in this work and its place in the project management discipline is established. There is a lot of interest in the development of Project Management Software (PMS). A new PMS categorization has been proposed. Next, we'll describe our project management software solution. Compared to other PMS, our web-based and collaborative PMS is praised. With the tool's design, we're primarily focused on making it easy to use and expand its capabilities.